The effect of underlying inflammation on iron metabolism, cardiovascular risk and renal function in patients with type 2 diabetes. Issue 3 (6th July 2021) - Ndevahoma, Fransina; Nkambule, Bongani B.; Dludla, Phiwayinkosi V.; Mukesi, Munyaradzi; Natanael, Kandiwapa N.; Nyambuya, Tawanda M.
Abstract: Aim: To investigate the impact of inflammation on iron metabolism, cardiovascular risk and renal function in type 2 diabetes (T2D). Methods: A total of 50 patients with T2D were included in this study. The patients were stratified into two groups based on their levels of C‐reactive protein (CRP), namely normal and high levels ( n = 25/group). All laboratory tests were measured using standardised methods. Results: Fasting plasma glucose levels were elevated in patients with high CRP when compared to those with normal levels ( p = 0.0413). Total serum iron levels were lower in patients with high CRP levels (12.78 ± 3.50) when compared to those with normal levels (15.26 ± 4.64), p = 0.0381. However, ferritin and transferrin levels were comparable between the groups ( p > 0.05). The mean cell volume (MCV) in the high CRP group was lower (87.66 ± 3.62) than the normal level group (90.79 ± 4.52), p = 0.0096, whilst the lipograms were similar ( p > 0.05). The estimated glomerular filtration rate (eGFR) was lower in the high CRP group (98.06 ± 11.64) than the normal level group (104.7 ± 11.11), p = 0.046. Notably, CRP levels were negatively associated with serum iron levels ( r = –0.38, p = 0.0061), MCV ( r = –0.41, p = 0.0031), potassium ( r = –0.37, p = 0.0086) and sodium levels ( r = –0.28, p = 0.0471). Regression analyses showed that only CRP ( β = –0.16, standard error [SE]: 0.06, p = 0.0125) and sodium ( β = 0.51, SE: 0.25, p = 0.0434) levels contributed significantly to the prediction of serum iron levels. Conclusion: Underlying inflammation in T2D is associated with increased incidence of hypertension and reduced levels of serum iron, MCV and renal function. Although there was no apparent clinical anaemia or renal dysfunction in these patients, mitigating inflammation may be effective in circumventing the ultimate development of iron deficiency anaemia and chronic kidney disease in T2D.